Hypermethylation of Mest promoter causes aberrant Wnt signaling in patients with Alzheimer’s disease - Renuka Prasad (Nature Portfolio, 2021)
Abstract Alzheimer's disease (AD) is a progressive neurodegenerative disorder that leads to dementia and behavioral changes. Extracellular deposition of amyloid plaques (Aβ) and intracellular deposition of neurofibrillary tangles in neurons are the major pathogenicities of AD. However, drugs targeting these therapeutic targets are not effective. Therefore, novel targets for the treatment of AD urgently need to be identified. Expression of the mesoderm-specific transcript (Mest) is regulated by genomic imprinting, where only the paternal allele is active for transcription. We identified hypermethylation on the Mest promoter, which led to a reduction in Mest mRNA levels and activation of Wnt signaling in brain tissues of AD patients. Mest knockout (KO) using the CRIPSR/Cas9 system in mouse embryonic stem cells and P19 embryonic carcinoma cells leads to neuronal differentiation arrest. Depletion of Mest in primary hippocampal neurons via lentivirus expressing shMest or inducible KO system causes neurodegeneration. Notably, depletion of Mest in primary cortical neurons of rats leads to tau phosphorylation at the S199 and T231 sites. Overall, our data suggest that hypermethylation of the Mest promoter may cause or facilitate the progression of AD.